Pengaruh Permainan Tradisional Egrang Batok Kelapa Dengan Kemampuan Gerak Dasar Lokomotor Anak Kelompok B - Munifa Kamu; Zubaidi, Mohamad; Laiya, Sri Wahyuningsi (Early Childhood Education Department, Faculty of Education, State University of Gorontalo, 2023)
The study's objective is to improve the locomotor basic movement skill of Group B children by utilizing the traditional game Egrang Batok Kelapa as a media tool at TK State Bersehati Binjeita Kindergarten in Bolangitang Timur District, North Bolaang Mongondow Regency. The locomotor skills include walking, running, and jumping. This quantitative research used an experimental method with a pre-test and post-test research design. The subjects were tested before and after the treatment was given.